MODEL HABITUASI SIKAP ANTI BULLYING BAGI SISWA SEKOLAH DASAR MELALUI PERMAINAN MENYENANGKAN - Sudirman Sudirman; Rusdianto Umar; M. Mujtaba Habibi (Jurnal Praksis dan Dedikasi Sosial (JPDS), 2022)
This article discusses the habituation model of anti-bullying attitudes for elementary school students. Habituation of anti-bullying attitudes must be carried out because the practice of bullying still occurs in schools so there must be a model that can be used to prevent bullying in schools. The purpose of applying this habituation model is to reduce bullying behavior in students, through instilling anti-bullying values in each student, it is hoped that bullying cases at the education level will not appear again. The method used in the application of the habituation model of anti-bullying attitudes is the preparation of a game/game model and the application/habituation of learning methods and anti-bullying games/games in schools. The results of the preparation and application of the habituation model resulted in an anti-bullying game with the instilled values of cooperation/collaboration, respect for differences, empathy, and sharing. The stages of implementing anti-bullying games are opening, welcoming, motivational, games (explanation, practice, distribution of prizes), reflection, and closing.Artikel ini membahas tentang model habituasi sikap anti bullying bagi siswa sekolah dasar. Habituasi sikap anti bullying harus dilakukan karena praktek bullying masih terjadi di sekolah sehingga harus ada model yang dapat digunakan untuk mencegah terjadinya bullying disekolah. Tujuan penerapan model habituasi ini adalah menurunkan perilaku perundungan (bullying) pada siswa, melalui penanaman nilai anti bullying dalam setiap diri masing-masing siswa, diharapkan kasus bullying di jenjang pendidikan tidak akan muncul lagi. Metode yang digunakan dalam penerapan model habituasi sikap anti bullying adalah penyusunan model permainan/game dan penerapan/habituasi metode pembelajaran dan permainan/game anti bullying di sekolah. Hasil penyusunan dan penerapan model habituasi dihasilkan sebuah permainan anti bullying dengan nilai yang ditanamkan adalah kerjasama/kolaborasi, menghargai perbedaan, empati, berbagi. Tahapan pelaksanaan penerapan game anti bullying adalah pembukaan, sambutan, motivasi, permainan (penjelasan, praktik, pembagian hadiah), refleksi, dan penutup.